Mangrove swamps victims of their own prosperity - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Mangrove swamps cove. more than 15 million hectares in tropical Africa, Asia, and Latin America, and today are one of the most threatened ecosystems on our planet not just because of their fragility, but particularly because of their prosperity....